The soluble transferrin receptor as a marker of iron homeostasis in normal subjects and in HFE-related hemochromatosis - Brandâo, M. (2010)
Background and Objectives. The soluble transferrin receptor (sTfR) is a clinical marker of erythropoietic activity, also used in the diagnosis of iron deficiency. In the present paper we explore the meaning of this parameter in normal physiological conditions of iron homeostasis and in the setting of iron overload due to hereditary hemochromatosis (HH). Design and Methods. Reference values for sTfR were established in a population of 42 apparently healthy subjects, analyzed in relation to other hematologic parameters, namely, hemoglobin (Hb), mean corpuscular volume (MCV), transferrin saturation (TfSat) and serum ferritin. The same analysis was done in a group of 45 patients with HH who were homozygous for the C282Y mutation of HFE and had a wide range of TfSat values. In addition, individual serial profiles were analyzed in three patients. Results. In normal subjects circulating sTfR correlated significantly with the TfSat level, reflecting the systemic effect of iron availability on the erythropoietic activity in a normal physiological steady state. A TfSat of 25% appeared as a threshold value, below which there was a progressive increase in sTfR; this increase in sTfR occurred concomitantly with a decrease in Hb, MCV and serum ferritin. In HH patients the up-regulation of sTfR started at TfSat values as high as 50%. Interpretation and Conclusions. The fact that sTfR up-regulation started at higher TfSat values in HH patients suggests that the recognition of systemic iron available for erythropoiesis is altered in this condition. Based on these results, a new hypothesis is advanced, proposing that the HFE protein in involved as a sensor of systemic iron availability, via the soluble transferrin receptor.